Fire and Explosion Hazard Risk Analysis of Fuel Transfer Activities at Fuel Terminal “X” Utilizing the Quantitative Risk Analysis (QRA) Method - Sulistyawan, Angga Wahyu; Yuliusman, Yuliusman (Journal of Materials Exploration and Findings, 2025)
Fuel transfer operations at Fuel Terminal ‘X’ constitute a critical stage in the energy supply chain, where complex interactions among human, technical, and environmental factors generate inherent risks of fire and explosion. The flammable nature of fuel oil, coupled with the possibility of vapor or liquid releases outcoming by tool failures, connection leaks, or control system malfunctions, underscores the need for robust and proactive risk management strategies. This study aims to evaluate and mitigate these risks by applying Quantitative Risk Assessment (QRA). The assessment utilized the Parts Count method to foercast generic component failure rates and Fault Tree Analysis (FTA) to classify potential failure pathways that could head to hazardous fuel release scenarios. Consequences were modeled with SAFETI software, enabling a detailed examination of thermal radiation spread by fires, overpressures by blasts, and the determination of risk exposure zones for human populations in the vicinity. Further application of control systems like gas leak detectors, flame detectors, and the automatic/manual shutdown and isolation systems reduced the IRPA to an acceptable risk level. These findings emphasize the importance of combining quantitative risk modelling and systematic safety barriers to improve the operational safety. It is anticipated that these results will support the preparation of risk assessment protocols and safety policy guidelines for fuel handling facilities in the oil and gas sector.